Energy, exergy and economics analysis of an ORC working with several fluids and utilizes smelting furnace gases as heat source. (March 2018) - Mirzaei, Mojtaba; Ahmadi, Mohammad Hossein; Mobin, Mohammad; Nazari, Mohammad Alhuyi; Alayi, Reza
Highlights: Thermodynamic and economic analysis are conducted on gases existing a metal smelting furnaces by applying different working fluids. Exergy analysis of an ORC Working with Several Fluids and Utilizes Smelting Furnace Gases as Heat Source. For a specific pressure ratio of a turbine, m-xylene, P-xylene and Ethylbenzene have higher thermal efficiency and net power output in comparison with other investigated fluids. Abstract: It is necessary to improve efficiency of energy systems due to lack of fossil fuels in near future and their environmental issues. Waste heat of industrial activities can be recovered in order to enhance the efficiency of the energy systems. Organic Rankine cycles (ORCs) are an appropriate option to recover heat from metal smelting furnaces. In this study, thermodynamic and economic analyses are conducted on an ORC working with the gases existing a metal smelting furnace by applying different working fluids. Effects of various parameters on the performance are investigated and the results are compared. Obtained results show that m-xylene, P-xylene and Ethylbenzene have higher net power output, higher efficiency and lower total cost compared with other investigated working fluids.